Omento alógeno de coelho (tecido ou cultivo) associado a membrana amniótica de cão na ceratoplastia lamelar em coelhos - Barros, Séfora Vieira da Silva Gouvêa de [UNESP] (2014)
The omentum, a fatty tissue rich in mesenchymal stem cells, expresses growth factors that act in tissue regeneration, making it attractive for use in regenerative medicine. To our knowledge, reports that investigate the use of omentum cells in ophthalmology have yet to be published. The purpose of this study was to assess the clinical and microscopic effects of omentum associated with amniotic membrane on the repair of rabbit cornea submitted to keratectomy. Two methods were evaluated; in the first, the omentum was covered with amniotic membrane immediately following its implantation on the cornea (OM group), while in the second, the amniotic membrane was colonized by omental progenitor cells and transplanted to the cornea (OMC group). Clinical parameters were evaluated from data collected up to 60 days postoperatively. The incidence and prevalence of chemosis were higher in the OM group (p<0.05). The OMC group showed greater incidence of blepharospasm (p<0.001). Under light microscopy, the absence of epithelium in the lesioned area and stromal disorganization were observed in the early postoperative period. After 60 days of evaluation, all the corneas were repaired. Intense cell proliferation was detected with Ki-67, in the final stages of the repair process, where amniotic membrane containing omental progenitor cells was transplanted to the corneas. The use of omentum and its cells, in association with amniotic membrane, favored the repair of the cornea and did not induce complications